Age, Gender and Seasonal Patterns of Asthma in Emergency Departments of Southern Puerto Rico - Montealegre, Federico; Bayona, Manuel; Chardón, Domingo; Treviño, Fernando (Puerto Rico Health Sciences Journal, 2012)
see manuscript